Residual entropy in the zero-temperature limit of toluene glass - Moratalla, M.; Bejarano, P.; Castilla, J.M.; Ramos, M.A. (Физика низких температур, 2019)
The specific heat Cp of toluene, doped with 2 mol% ethanol to avoid rapid crystallization, has been measured in both glass and crystal states, and with special accuracy at low temperatures in the range 1.8−20 K using the thermal relaxation method. By making use of the complementary Cp curves measured in the reference crystal state, we have been able to obtain the entropy curve of the glass and eventually the residual entropy of toluene glass in the zero-temperature limit, that is found to be 5.1 J/(K⋅mol). This value is clearly lower than others previously reported in the literature, which lack the knowledge of the particular specific-heat behavior of glasses at low temperatures and hence overestimated the glass residual entropy at zero temperature. In addition, we have studied in detail such low-temperature “glassy anomalies” in the case of toluene, extending and improving previous measurements. The surprising depletion previously reported of tunneling two-level systems in toluene glass has been confirmed, though this fact coexists with the presence of a broad peak typical of glasses (the socalled boson peak) in Cp/T³ at 4.5 K. For the toluene crystal, the expected cubic Debye behavior has been found at lower temperatures.